Paradigm Shift: New Ideas for a Structural Approach to NCD Prevention; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Ashley Schram; Sharni Goldman (Kerman University of Medical Sciences, 2020)
It is a well-documented fact that transnational corporations engaged in the production and distribution of health-harmful commodities have been able to steer policy approaches to address the associated burden of non-communicable diseases (NCDs). While the political influence that corporations wield stems in part from significant financial resources, it has also been enabled and magnified by what has been referred to as global health's neoliberal deep core, which has subjected health policy to the individualisation of risk and responsibility and the privileging of market-based policy responses. The accompanying perspective article from Lencucha and Thow draws attention to neoliberalism in the NCD space and the way it has historically structured patterns of thinking and doing that foreground economic interests over health considerations. In this commentary, we explore how shifting from a focus on material power to discursive power creates space to see the NCD agenda as a battle of economic ideas as well as dollars, and consequently the importance of public health engagement in the next vision for the economy.